2011
DOI: 10.3329/jsr.v3i2.7128
|View full text |Cite
|
Sign up to set email alerts
|

Study on Isolation and Identification of <i>Salmonella</i> and <i>Escherichia coli</i> from Different Poultry Feeds of Savar Region of Dhaka, Bangladesh

Abstract: The study was conducted aiming at the isolation and identification of Salmonella and Escherichia coli (E. coli) from different brands of poultry feeds sold in Savar, Dhaka, Bangladesh. Seven different poultry feeds were subjected to microbiological analysis. All these samples were analyzed by culturing in different media such as nutrient broth (NB), nutrient Agar (NA), SS Agar (Salmonella-Shigella Agar), BGA (brilliant-green Agar), Mac Conkey, DHL and EMB (eosin methylene blue) media. Total bacterial colonies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 12 publications
2
21
1
Order By: Relevance
“…Possible reason for the absence of fungal count in feed sample A, B and C might be inclusion of antifungal agents, use of high temperature during preparation and manufacturing. The study showed that the percentage occurrence of E. coli was 65% (Table 5) which is in line with the findings of Akond et al (2009), Chowdhuri et al (2011) andDa Costa et al (2007) where it was 58%, 57.14% and 50% respectively. On the other hand the percentage of Salmonella spp.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Possible reason for the absence of fungal count in feed sample A, B and C might be inclusion of antifungal agents, use of high temperature during preparation and manufacturing. The study showed that the percentage occurrence of E. coli was 65% (Table 5) which is in line with the findings of Akond et al (2009), Chowdhuri et al (2011) andDa Costa et al (2007) where it was 58%, 57.14% and 50% respectively. On the other hand the percentage of Salmonella spp.…”
Section: Discussionsupporting
confidence: 90%
“…The feed samples were processed as described by Chowdhuri et al (2011) by homogenizing 10 gms of each sample in 90 ml of peptone water in the beaker and mixed thoroughly. Then 900 μl PBS was taken to each of the small bottles accordingly.…”
Section: Isolation and Identification Of Bacterial Isolates 251 Bamentioning
confidence: 99%
See 1 more Smart Citation
“…Contamination of food pathogens in animal feeds and foods has been a major concern in the distribution and storage of the products worldwide [1,2]. Among various preservations, biopreservation using natural derived compounds is more preferable compared to synthetic chemicals [3].…”
Section: Introductionmentioning
confidence: 99%
“…Contamination mainly by moist environment of market and poultry house, poultry feeds, unhygienic practice of farm handlers and surrounding environment 4. Another study was done to detect the Salmonella contamination rate from poultry feeds, where 71.43% Salmonella was detected from poultry feeds from different market in Savar area 38 .…”
Section: Bangladesh Scenariomentioning
confidence: 99%